Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1097/01202412-200110040-00013
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric Study of Growth Plate Subjected to Different Mechanical Conditions (Compression, Tension and Neutralization): An Experimental Study in Lambs Mechanical Growth Plate Behavior

Abstract: SUMMARYWe studied the morphologic effect of low mechanical stresses compression, tension and neutralization) (on the growth cartilage with an external fixator in 18 young lambs. On radiography, we only found more length in the femora subjected to tension (P<0.05). Bony bridges were not present, nor were there signs of altered vascularization or Ranvier's perichondral ring. Histomorphometrically, in the group subjected to tension, the germinative layer in the femur was higher (P<0.001) in the bones that had und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…In this study, gross measurements of the femoral length demonstrated restricted growth in the HC group, which is evidence of growth inhibition. Histomorphometry is reported also to be an accurate study to confirm delayed growth [Weise et al, 2001], and the measurement of the height of the growth plate or individual cell layer is a good quantitative method [Glickman et al, 2000;Arriola et al, 2001]. Shrinkage of dimension in the whole growth plate was observed in the HC group in this study.…”
Section: Discussionmentioning
confidence: 72%
“…In this study, gross measurements of the femoral length demonstrated restricted growth in the HC group, which is evidence of growth inhibition. Histomorphometry is reported also to be an accurate study to confirm delayed growth [Weise et al, 2001], and the measurement of the height of the growth plate or individual cell layer is a good quantitative method [Glickman et al, 2000;Arriola et al, 2001]. Shrinkage of dimension in the whole growth plate was observed in the HC group in this study.…”
Section: Discussionmentioning
confidence: 72%
“…Static compression applied to growth plates decreases longitudinal growth rates (Stokes et al, 2005;Bonnel et al, 1983;Wilson-MacDonald et al, 1990). Consistently, static tension increases longitudinal growth rates (Arriola et al, 2001;Stokes et al, 2006Stokes et al, , 2007WilsonMacDonald et al, 1990). The effect of applied stress level is linearly related to the percentage growth modulation (Bonnel et al, 1983;Stokes et al, 2006).…”
Section: Introductionmentioning
confidence: 76%
“…Extensive data exists to support the hypothesis that mechanics is involved in growth modulation (Stokes et al, 2005;Bonnel et al, 1983;Wilson-MacDonald et al, 1990;Robling et al, 2001;Arriola et al, 2001;Stokes et al, 2006Stokes et al, , 2007. Static compression applied to growth plates decreases longitudinal growth rates (Stokes et al, 2005;Bonnel et al, 1983;Wilson-MacDonald et al, 1990).…”
Section: Introductionmentioning
confidence: 94%
“…This cortex contains canals through which the epiphyseal vessels penetrate, expand into terminal spurs, and nourish the upper zones of the physis. 33 The metaphyseal circulation serves to calcify and ossify the primary spongiosa rather than to nourish the physis. The distinct effect of damage to these two separate epiphyseal and metaphyseal vascular networks has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The distinct effect of damage to these two separate epiphyseal and metaphyseal vascular networks has been demonstrated. 33 Metaphyseal ischemia leads to failure of ossification and consequent elongation of cartilage columns until the blood supply is restored. Suppression of the epiphyseal circulation, in contrast, causes an infarction of the physis.…”
Section: Discussionmentioning
confidence: 99%